Pyruvate-Enriched Oral Rehydration Solution Improves Glucometabolic Disorders in the Kidneys of Diabetic db/db Mice - Xiao Meng Zhang; Hao Deng; Jin Dong Tong; Yi Zhen Wang; Xu Chao Ning; Xiu Hong Yang; Fang Qiang Zhou; Hui Min Jin (Journal of Diabetes Research)
Diabetes is prevalent worldwide, but ideally intensive therapeutic strategy in clinical diabetes and diabetic nephropathy (DN) is still lack. Pyruvate is protective from glucometabolic disturbances and kidney dysfunction in various pathogenic insults. Present studies focused on oral pyruvate effects on diabetes status and DN with 0.35% pyruvate in pyruvate-enriched oral rehydration solution (Pyr-ORS) and 1% pyruvate as drinking water for 8 weeks, using the model of diabetic db/db mice. Both Pyr-ORS and 1% pyruvate showed comparable therapeutic effectiveness with controls of body weight and blood sugar, increases of blood insulin levels, and improvement of renal function and pathological changes. Aberrant key enzyme activities in glucometabolic pathways, AR, PK, and PDK/PDH, were also restored; indexes of oxidative stress and inflammation, NAD+/NADH ratio, and AGEs in the kidneys were mostly significantly preserved after pyruvate treatments. We concluded that oral pyruvate delayed DN progression in db/db mice and the modified Pyr-ORS formula might be an ideal novel therapeutic drink in clinical prevention and treatment of type 2 diabetes and DN.